COVID-19 aus Sicht der Neurologie - Simon, Ole J.; Timmermann, Lars (DMW - Deutsche Medizinische Wochenschrift, 2020)
Evidence of neurological complications and direct affection of neuronal structures in the course of infections with SARS-CoV-2 is actually emerging. Therefore adequate medical care for neurological patients must also be guaranteed as part of the current SARS-CoV-2 pandemic. Multiple, peripheral and central neurological affections have been described, such as particular headache, consciousness disorders, cranial nerve disorders, peripheral nerve damage, epileptic seizures and ischemic events. Since abundant information on COVID-19 is published on a daily basis, this article aims to summarize and evaluate the current literature on this topic.
Keywords: SARS-CoV-2; COVID-19; neurologische Komplikationen; ischämischer Schlaganfall